Pengendalian Proses Pada Katalitik Pirolisis Serabut Kelapa Sawit Dengan Menggunakan Reaktor Batch - Wulandari, Yeni Ria; Rezki, Amelia Sri; Afifah, Dian Ayu; Hamdi, Rafiqul (REACTOR: Journal of Research on Chemistry and Engineering, 2024)
Indonesia is the largest producer of palm oil in the world. The palm oil industry always produces solid waste, one of which is palm fiber. Palm fiber can be processed into chemicals or renewable fuels. Catalytic pyrolysis is a pyrolysis process using a catalyst, the purpose of pyrolysis using a catalyst is to upgrade the product. In this study, the pyrolysis process was carried out in a batch reactor with controlled temperature. Catalytic pyrolysis was carried out at a temperature of 400oC with a catalyst to oil palm fiber ratio of 1:2. The control system uses a feedback controller system. Pyrolysis of palm fiber with Al white and NiCl (II) catalysts produces bio-oil products with the highest yield. Pyrolysis with Al2O3 catalyst produces higher Bio-char products. The density of the water phase bio-oil is close to the density of water, and the viscosity of the bio-oil with the oil phase is more than 10 Cp. Based on GC-MS analysis, the largest component in bio-oil is acetic acid. Bio-oil and Bio-char pyrolysis products have the potential as new chemicals, renewable energy and adsorbents.